Chronic lymphocytic leukemia manifested by steroid responsive polyneuropathy (Faculty of Medicine Universitas Indonesia, 2003)
We report a patient of acute demyelinating polyneuropathy who on investigations turned out to be suffering from chronic lymphocytic leukaemia (stage 0). Response to steroid therapy suggests an autoimmune process as a cause of polyneuropathy. Chronic lymphocytic leukaemia manifested by acute polyneuropathy has been described rarely in literature. (Med J Indones 2003; 12: 27-8) Keywords: chronic lymphocytic leukemia; acute demyelinating polyneuropathy